Motorcycle image tracking and edge detections based on Simulink software - Mat Nong, Mohd Ali; Osman, Rosiah; Md Yusof, Juraina; Mohd Sidek, Roslina (IEEE, 2016)
A visual driver support system was developed to reduce accidents involving motorcyclist. The system used Matlab software as a platform to detect motorcycle image. The detection system was designed to detect still images and moving objects images for different resolutions. A motorcycle was defined as the target object in this case. The results showed that the visual driver support system is able to detect image of motorcycle in still and in moving condition. The percentage of correct detection of motorcycle image is 83.3% and 50% for low and high image resolutions respectively.